BEHAVIORISTIC LEARNING THEORY AND ITS APPLICATIONS IN LEARNING - Lika; Neviyarni; Herman Nirwana (Yayasan Citra Dharma Cindekia, 2021)
Learning is an effort to master something new through the process of interaction due to encouragement and responses from individuals. The concept of behaviorism is a concept to explore human behavior caused by the stimulus and response . Skinner argues that learning is a reciprocal relationship between stimulus and response caused by interaction activities with the environment, therefore behavior changes occur in individuals. Therefore, this behavioristic learning theory emphasizes the process of forming individual behavior from bad behavior to good behavior.